Case Report: Persistent delusional memories after postoperative delirium in a woman with complex cardiac surgical history - Stańska, Aleksandra; Klapkowski, Andrzej; Karolak, Wojciech; Brzeziński, Maciej (Frontiers in Psychiatry, 2026)
IntroductionDelirium is common after cardiac surgery and is associated with long-term cognitive and psychological morbidity. Many patients later recall vivid, often frightening delusional experiences, but sustained delusional conviction in such memories long after delirium resolution is rarely reported.Case descriptionWe describe a woman in her late 60s with congenital aortic valve disease, three previous aortic valve operations and a recent tricuspid valve repair via right mini-thoracotomy. Her postoperative course was severely complicated by hemothorax, repeated thoracotomies, respiratory failure, sepsis, acute kidney injury, anemia and malnutrition, together with exposure to multiple centrally acting drugs (benzodiazepines, opioids, pregabalin, dexmedetomidine). While being treated on a general cardiothoracic ward she developed delirium, with disorientation, sleep-wake disruption and prominent persecutory and somatic delusions that staff were mocking her, taking humiliating photographs and “videos”, and forcing tablets into her throat. Delirium resolved with optimization of medical status, reduction of deliriogenic medications and short-term low-dose olanzapine, yet she retained a fixed belief that these ward events had truly occurred. For almost a year, including during a later admission for prosthetic valve endocarditis with paravalvular leak and an unsuccessful percutaneous closure attempt, she repeatedly reported these experiences as factual abuse despite psychotherapy and psychoeducation. Only during a subsequent elective admission, when reconsidering a high-risk redo valve operation that she ultimately declined, did she spontaneously reframe the memories as symptoms of “a mental disorder” and apologize to staff.ConclusionThis case highlights how delirium-related persecutory experiences can consolidate into persistent trauma-like autobiographical memories with prolonged delusional conviction, and underscores the need for structured delirium follow-up, explicit psychoeducation for patients and families, and close collaboration between cardiology, cardiac surgery, psychiatry and psychology.